Crisis y capitalismo: el riesgo implícito en la metamorfosis de la mercancía - Barrera Herrera, Jorge (2012)
This article reviews some aspects little studied by researchers and economists who are concerned with the different inter-relations of capital, value and work in an environment of constantly changing techno-scientific, rational use of natural resources and their influence on the process of transformation of the goods from occurring until it makes its unsecured sale, raising some arguments explaining how it is that in a dependent capitalist society like ours, and in fact can be are currently presenting and crises elsewhere and which are not shielded.